Life’s Forces That Sustain and Drive Our Existence Towards. Efforts of Steering One’s Life Through Time - Bellini, Bianca (ETHICS IN PROGRESS, 2017)
We always live in the present and we always pass through the present, even if we constantly reach out towards the future and towards the past. We move towards an effort of shaping the future and towards an effort of comprehending the past. Our experience of time flows into a relentless stream that inexorably points towards. This entails that the way we experience time is inescapably interwoven with a necessity of giving a direction to this movement towards. Such a necessity brings to light two pivotal questions: how to describe such a relentless movement forwards? Which forces can we rely on to drive our existence towards? This research aims at pinpointing such forces and, in so doing, outlining a phenomenological picture of our multilayer experience of time.